Hepatoprotective effects of silymarin in management of liver injury caused by tuberculosis treatment - Yeong Yeh Lee; Vincent Tee (BioExcel Publishing Ltd, 2023)
Tuberculosis (TB) is a chronic infection of global-health concern because of its high incidence, costly medical treatment, drug resistance and risk of co-infections. Anti-TB treatment involves a combination of drugs with high degree of liver toxicity, leading to drug-induced liver injury in 2-28% of patients who receive anti-TB treatment. In this case report, a patient with TB experienced drug-induced liver injury, and the initiation of treatment with silymarin 140 mg three-times daily resulted in a significant hepatoprotective effects as shown by the decreased liver enzyme activity. This article is part of the Current clinical use of silymarin in the treatment of toxic liver diseases: a case series Special Issue: https://www.drugsincontext.com/special_issues/ current-clinical-use-of-silymarin-in-the-treatmentof- toxic-liver-diseases-a-case-series